SISTEM BERTANI PADI SAWAH BAGI ORANG BUGIS DI DESA NELOMBU KECAMATAN MOWEWE KABUPATEN KOLAKA TIMUR - Irham Arno; Sarlan Adijaya (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study aims to find out and describe the farming methods of the Bugis people in Nelombu Village, to find out and describe why the Bugis people in Nelombu Village still maintain the way of farming rice fields. The method used in this study was a qualitative descriptive method in which the researcher attempted to describe, describe and explain the process of rice farming for the Bugis people. Using purposive techniques and direct observation in the field. The data collected was then analyzed. The results of this study are: 1). The way of farming paddy rice in the Bugis people is holding tudang sipulung (sitting together in deliberations), ma'jama galung (land management), mattabela (scattering seeds), mappajo-pajo (installing scarecrows), mappasule' (transferring seeds to non-growing land), mappamula ase (beginning of harvest), mingala ase (harvest on black glutinous rice), mappeppe ase pulu lotong (threshing of glutinous rice) and mallampu ase pulu (peeling of skin on glutinous rice). 2). The reason why the Bugis people still maintain the way of paddy rice farming is because the first is lowland rice farming which is a hereditary tradition and the second is lowland rice farming supported by the natural environment.